Sequencing extended monetary policies at the effective lower bound - Yang Zhang; Lena Suchanek; Jonathan M. Swarbrick; Joel Wagner; Tudor Schlanger (Bank of Canada, 2021)
In response to the global COVID-19 pandemic, the Bank of Canada aggressively lowered its policy interest rate and provided additional easing using forward guidance and quantitative easing. In this analysis, we use simulations in the Bank of Canada's projection model-the Terms-of-Trade Economic Model-to consider a suite of extended monetary policies (EMPs) to support the economy following the COVID-19 crisis. We focus on the implementation sequencing of three EMP options when the policy rate is at the effective lower bound: credit easing, forward guidance and quantitative easing. We find that the policy mix that delivers the best outcome for the Canadian economy calls for immediately implementing forward guidance and quantitative easing, followed by credit easing when containment measures are lifted. Furthermore, going "full scale" and implementing all available EMP options effectively helps stabilizing the economy because each of these tools reinforces the others. We also quantify the fiscal response needed to offset the gap in gross domestic product created by the effective lower bound, given operational limitations in scaling up EMPs.
Keywords: E3; E4; E5; E52; E58; 330; Coronavirus disease (COVID-19); Monetary policy; Monetary policy transmission